Growth of Delafossite CuCr1−xMxO2 Systems and Their Anisotropic Magnetization - Markus Diantoro; Agustinus Agung Nugroho; J. Baas; G. Blake; T. T. M. Palstra (Jurnal Fisika dan Aplikasinya, 2011)
The effort to obtain a good crystalline state of delafossite CuCrO2 phase is becoming important along with their potential application and scientific important results. In this paper we report the result of crystal growth and their Magnetic and Electric Capacitance Measurements. We focused on two methods i.e. flux decomposition (FD), and Bi2O3 Flux Growth (FB). The starting materials for FD growth were K2Cr2O7 and CuO taking the advantage of the potassium dichromate’s decomposition. In case of FB flux growth, we should prepare the correct molar ratio for CuCrO2 pellet on the Bi2O3 powder in 1 : 6 ratio. It is found that both methods are possible to obtain crystalline phases along with their specific technical processes to be overcomed. We show that FB method resulted flaky shapes while FD method produced rather bulky morphology. The obtained samples were checked by CAD4 single crystal diffractometer for their lattices and MPMS-SQUID magnetometer for their magnetization for different orientation. We check also the electric capacitance at the range of 5 K to 300 K along c lattice direction. It is found that their single Neel temperature (TN) fall around 25 K. A distinct anisotropy of magnetization profiles shown by its crystal directions and planes. On the other hand the out of plane electric capacitance of Mn doped crystal did not show any transition at the range of 5 K to 300 K.